MAKNA SIMBOL GERAK TARI JEPIN LANGKAH PENGHIBUR PENGAN BENTUK PENYAJIAN TARI JEPIN LANGKAH SERONG DI KELURAHAN BATU LAYANG KECAMATAN PONTIANAK UTARA - Mina Muthiasari; Ismunandar Ismunandar; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the presentation form of Jepin Langkah Serong Dance in Batu Layang Village, North Pontianak District, West Borneo and to complement the research data. The problem of this research is related to the elements of the presentation form of the Langkah Serong Jepin Dance. This study uses a descriptive method with a qualitative form and uses a choreographic approach. Data collection techniques in the form of observation, interviews, and documentation. Based on the data analysis, it is concluded that the form of the presentation of the Jepin Langkah Serong Dance in Batu Layang Village, North Pontianak District, West Kalimantan. This Jepin Langkah Serong Dance is an entertainment dance. The Jepin Langkah Serong Dance has 4 types. The musical instruments the Jepin Langkah Serong Dance are the lute, tar, long drum, violin and accordion. The Jepin Langkah Serong Dance uses realist make up, clothes worn by female dancers with brackets, gill cloth, pandanus folded head bun, flowers, for the male dancers wearing telok belangga, gill-patterned cloth, and cap on theor head.Keywords: Dance, Serong Langkah Jepin, Form Of Presentment